The Role of Health Extension Workers in Primary Health Care in AsgedeTsi'mbla District: A Case of Lim'at T'abya Health Post - Desta, Seare Hadush; Basha, Shaik Yousuf (International Journal of Social Sciences and Management, 2017)
Health Extension Workers are the health service providers to the community in delivering integrated preventive, promotive and basic curative health services. Hitherto no studies have been carried out in Lim ‘at T’abya health post focusing on the role of health extension workers. Thus the researcher has randomly selected 263 participants in order to achieve the intended objectives of the study. The researcher used both quantitative and qualitative approaches. The result of the study identified the major Health Extension Program services which are delivered by Health Extension Workers in the health post to seek malaria treatment, child immunization and Antenatal Care followed by Postnatal Care, family planning, referral for delivery, diarrhea treatment and health education. The challenges of Health Extension Workers hindering their performance for the unsuccessful health service provision identified as strong societal cultural beliefs, remoteness, poor relation with supervisors, communication system and road construction, low remuneration, lack of refresher courses and improper attention by Qebelle administrators to health agendas. Attitude of community towards Health Extension Workers communication skill, quality of service provision and social behaviors is over all positive but the following up of referred patients and the skill to diagnosing community health problems that Health Extension Workers need to work sensitively which are answered negatively by the respondents. To increase community’s health post utilization, health posts should be equipped with minimum essential medical equipment with particular focus on malaria treatments, family planning, deliver, treatment of common illnesses and immunization services in the study area. Int. J. Soc. Sc. Manage. Vol. 4, Issue-4: 248-266